Cognitive hallmarks of insomnia and its influence on cardiac response to handgrip test among medical students - Agbaraolorunpo, Francis M.; Ogunyemi, Adedoyin; Ogunlunsi, Kehinde; Jimoh, Wale (International Journal Of Community Medicine And Public Health, 2024)
Background: Sleep disturbance, particularly insomnia, is increasingly prevalent among university students, and is associated with risk of cardiovascular disease in general population. The study investigated predictors of insomnia and its impact on cardiovascular responsiveness among undergraduates at the University of Lagos, Nigeria. Methods: A cross-sectional survey was conducted on 514 students categorized into normal or insomnia groups based on their insomnia severity index (ISI) scores. The association between insomnia and various factors related to poor sleep was assessed. Systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) responses to a handgrip test at 30% maximum voluntary contraction (MVC) were compared between the two groups (n=57) using t-tests. Results: Predictors of insomnia among students included environmental discomfort, engagement in digital activities, emotional and health challenges, use of sleep suppressants, and academic stress, all significantly associated with insomnia (p<0.001). Other factors associated with insomnia included low mood, attention deficit, memory loss, and poor academic performance (p<0.01). Average SBP and DBP were significantly higher (p<0.05) in control group compared with insomnia group. Conclusions: Low mood, attention deficit, memory loss and poor academic performance are hallmarks of insomnia among medical students, with no potential cardiovascular risk.